Challenges in granular physics - Halsey,Thomas; Mehta, Anita (New Jersey World Scientific, 2003)
This book contains accounts of modern approaches to the physics of particulate matter, from a broad group of interdisciplinary and international experts in the field. It will serve as an invaluable handbook for all researchers, both novices and experienced people, who want to be quickly guided to open-ended questions in key aspects of the field. challenge and this topic.
Keywords: Cơ Bản